2005
DOI: 10.1111/j.1440-1673.2005.01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of tubular colonic duplication by barium follow‐through study

Abstract: Barium enema studies are considered essential for the diagnosis of tubular colonic duplication with opacification of two colons being the diagnostic sign. Yet in certain cases, barium enema apparently does not show positive findings. A case is reported in which a barium follow-through study established the complete diagnosis of duplication of colon and terminal ileum. The findings were confirmed on laparotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Ultrasound is particularly well suited for the identification and characterization of duplication cysts, although in our case it was inconclusive (15)(16). Contrast examinations of the gastrointestinal tract can be useful in order to demonstrate displaced loops of bowel surrounding the presumed cyst and depict the communication with the gastrointestinal tract (17). In our case the use of contrast in the Barium Enema study revealed the origin of the cystic structure and depicted the communication with the transverse colon.…”
Section: Discussionmentioning
confidence: 80%
“…Ultrasound is particularly well suited for the identification and characterization of duplication cysts, although in our case it was inconclusive (15)(16). Contrast examinations of the gastrointestinal tract can be useful in order to demonstrate displaced loops of bowel surrounding the presumed cyst and depict the communication with the gastrointestinal tract (17). In our case the use of contrast in the Barium Enema study revealed the origin of the cystic structure and depicted the communication with the transverse colon.…”
Section: Discussionmentioning
confidence: 80%
“…Contrast enema and a fistulogram performed concomitantly, preferably with contrast media of differing densities, helps to delineate both colons. Occasionally, upper gastrointestinal contrast follow-through studies may help to locate the proximal extent of duplication [ 10 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peristalsis of the cyst wall has also been noted on ultrasound scan [11] . Contrast barium enema may show communication between the duplication and the normal bowel, with opacification of the two colons [12] ; the communication between the duplication cyst and main pancreatic duct may be seen by endoscopic retrograde cholangiopancreatography [13] . Besides this, technetium scan may demonstrate ectopic g astric mucosa in duplication [14] .…”
Section: Discussionmentioning
confidence: 99%